Evaluation of the Policy on the Registration and Structuring of Civil Society Organizations in Pandeglang Regency - Nasir Nasir; Untung Saritomo; Devina Devina (ijd-demos, 2024)
Abstract The rapid growth in the number of civil society organizations (CSOs) known locally as ormas in Pandeglang Regency has not been matched by administrative orderliness or official registration, thereby complicating local government oversight efforts. This study aims to evaluate the implementation of policies regarding CSO registration and management in Pandeglang Regency, as well as to analyze the factors that hinder or support this process. A descriptive qualitative research method was employed. Data collection involved in-depth interviews, observation, and document analysis at the Pandeglang Regency National Unity and Politics Agency (Kesbangpol), with informants comprising government officials, CSO administrators, and community leaders. The findings indicate that the implementation of CSO registration policies has not been optimal. Key obstacles identified include limited human resources for oversight, weak inter-agency coordination, and low legal awareness among CSO administrators regarding registration obligations. The study highlights the need to digitize the registration system and increase the frequency of periodic guidance and supervision. In conclusion, the management of CSOs in Pandeglang Regency requires service system reform and the strengthening of local regulations to foster more transparent and accountable organizational governance. Keywords: Policy Evaluation; CSO Registration; Organizational Management; Pandeglang.